Chemical Synthesis and Applications of Colloidal Metal Phosphide Nanocrystals - Li, Hui; Jia, Chao; Meng, Xianwei; Li, Hongbo (Frontiers in Chemistry, 2019)
Colloidal nanocrystals (NCs) have emerged as promising materials in optoelectronic devices and biological imaging application due to their tailorable properties through size, shape and composition. Among these NCs, metal phosphide is an important class, in parallel with metal chalcogenide. In this review, we summarize the recent progress regarding the chemical synthesis and applications of colloidal metal phosphide NCs. As the most important metal phosphide NCs, indium phosphide (InP) NCs have been intensively investigated because of their low toxicity, wide and tunable emission range from visible to the near-infrared region. Firstly, we give a brief overview of synthetic strategies to InP NCs, highlighting the benefit of employing zinc precursors as reaction additive and the importance of different phosphorus precursors to improve the quality of the InP NCs, in terms of size distribution, quantum yield, colloidal stability and non-blinking behavior. Next, we discuss additional synthetic techniques to overcome the issues of lattice mismatch in the synthesis of core/shell metal phosphide NCs, by constructing an intermediate layer between core/shell or designing a shell with gradient composition in a radial direction. The chemical synthesis of other metal phosphide NCs, such as II-V metal phosphide NCs (Cd3P2, Zn3P2) and transition metal phosphides NCs (Cu3P, FeP) is subsequently introduced. We finally discuss the potential applications of colloidal metal phosphide NCs in photovoltaics, light-emitting diodes and lithium ion battery. An overview of several key applications based on colloidal metal phosphide NCs is provided at the end.